Hubungan Perilaku Minum Teh Dengan Kadar Hemoglobin Pada Mahasiswa STIKes Guna Bangsa Yogyakarta - Relita Pebrina; Ikrimah Nafilata; Sunartono Sunartono; Fransiska Aselina (Journal of Health (JoH), 2019)
Iron has an important role in the body that functions to transport oxygen from the lungs to all body tissues through hemoglobin in the blood. Iron deficiency is one of the factors causing anemia. Anemia can be diagnosed from a level of hemoglobin. If a person's has Hb level is low, it can be said that the person is suffering from anemia. The low Hb level can be influenced by several factors, one of which is the consumption of tea. The content of tannins in tea can reduce iron absorption by the body. This study aims to analyze the relationship between drinking of tea behavior in STIKES Guna Bangsa Yogyakarta students with level of hemoglobin. The method is carried out by direct interviews with 55 samples of female students and level of henoglobin were checked using the Hb meter automatic. The results obtained were that 71% of the samples consumed tea and 29% did not consume tea. 53.85% of the sample who consumed tea had a low Hb level whereas 68.75% of the samples that did not consume tea had normal Hb levels. Data from the results of chi-square analysis obtained a value of p = 0.001 <0.05, which means that there is a relationship between the behavior of tea drinking with hemoglobin levels in STIKES students for Yogyakarta